Kompetensi Manajerial Kepala Sekolah Dalam Program Sekolah Penggerak di SMP Negeri 4 Jombang - Kustomo Kustomo (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The Driving School Program is a collaborative program between the Ministry of Education and Culture and Local Governments which is followed by education units from primary to upper secondary levels. Through the driving school program, it is expected to realize the vision of Indonesian education. In the transformation process through the driving school program at SMP Negeri 4 Jombang, the principal has carried out his managerial competency function by planning, organizing, implementing and supervising. In addition, in order to adjust the school to the driving school program, the Principal of SMP Negeri 4 Jombang has a commitment to increase innovation including IT-based learning, school entrepreneurship programs and improving the character of students through religious activities.